Nasal Deformity Due to Tuberculous Chondritis - Moon, Soo-youn (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2014)
Tuberculosis (TB) is a common disease worldwide. However, nasal TB is quite rare, and the diagnosis of nasal TB requires a high index of suspicion. The most common symptoms of this unusual presentation are nasal obstruction and nasal discharge. We present a case of nasal TB with involvement of the hard palate presenting with a chronically progressive nasal deformity and ulceration of the hard palate. A biopsy confirmed the diagnosis, and medication for TB was started and the lesions resolved. When a patient presents with chronic ulcerative lesions that do not respond to antibiotic treatment, TB should be included in the differential diagnosis. Biopsy of the lesion can aid in the confirmation of the diagnosis.